Strategi Pengembangan Ekowisata Mangrove Batu Lumbang Desa Pamogan, Kecamatan Denpasar Selatan, Kota Denpasar - I Made Budiasa; Ida Ayu Made Dwisusanti; Vitalis Abun (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
This research is about the Development Strategy of Batu Lumbang Mangrove Ecotourism in Pamogan Village, South Denpasar District, Denpasar Regency. The purpose of the research is to identify internal and external factors and to find out what strategies are appropriate for the development of Batu Lumbang Mangrove Ecotourism. The location determination in this study used the purposive sampling method with a total of 33 respondents. The data collection methods used are interviews, literature studies, observations, and documentation. The data analysis method uses SWOT and QSPM analysis. The results of the research: a) by improving facilities and infrastructure such as improving access to roads, bridges and parking lots and adding other facilities such as clean public toilets, gazebos and garbage cans so that they can be used for the development of Batu Lumbang Ecotourism, b) by maximizing promotion through digital marketing, namely by utilizing social media, websites, and online booking platforms to promote ecotourism. In addition, organize events or festivals related to mangroves to attract tourists, c) improve the development of information centers complete with maps, information about mangroves, and local MSME products, d) Market penetration, namely by maximizing promotion by offering uniqueness in addition to natural beauty, biodiversity. The priority strategy is strategy one, improving facilities and infrastructure such as improving access to roads, bridges and parking lots and adding other facilities such as clean public toilets, gazebos and garbage cans so that they can be used for the development of Batu Lumbang Ecotourism with a TAS value (7.99).